How management tools holistically support enterprises' operation in supply chains? - Treven, Sonja (Array, 2019)
The paper examines how utilization of management tools supports enterprises’ operating in supply chains. The paper critically reviews the results of a previous, survey-based study, with a sample of 198 employees from Slovenian organizations, who assessed utilization of management tools in their organizations. With hierarchical regression analysis authors test the associations between management tools’ usage and enterprises operating in supply chain; the impact was controlled with the most significant personal and organizational drivers of management-tools usage. Results show that loyalty management, core competences, and scenario and contingency planning are most strongly associated with the supply chain management’s activities in organizations. The traditional supply chain management’ tools, like outsourcing, lean production and total quality management, are currently not considered to be important vehicles for supporting enterprises’ participation in supply chains. The results from this study suggest rethinking of the current focus of management tools utilization, when organizations try to improve their participation in supply chains. More management tools were measured than in earlier studies regarding management tools, supporting enterprises’ participation in supply chain; relations between management-tools utilization and enterprise participation in supply chain were empirically examined. In addition, the most commonly used management tools were considered simultaneously, which had not been done in prior studies.